The Last Ottomans: The Muslim Minority of Greece 1940–1949 - Sotirios Dimitriadis (Slovo, 2012)
The Last Ottomans: The Muslim Minority of Greece 1940–1949. [Series: New Perspectives on South-East Europe.] By KEVIN FEATHERSTONE, DIMITRIS PAPADIMITRIOU, ARGYRIS MAMARELIS and GEORGIOS NIARCHOS. Pp. 368. Basingstoke: Palgrave Macmillan. 2010. £68. Hardback. ISBN: 9780230232518. Click here to read the full review.